2004
DOI: 10.1073/pnas.0406361102
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-binding drugs offset tau sequestration by stabilizing microtubules and reversing fast axonal transport deficits in a tauopathy model

Abstract: We tested the hypothesis that microtubule (MT)-binding drugs could be therapeutically beneficial in tauopathies by functionally substituting for the MT-binding protein tau, which is sequestered into inclusions of human tauopathies and transgenic mouse models thereof. Transgenic mice were treated for 12 weeks with weekly i.p. injections of 10 or 25 mg͞m 2 paclitaxel (Paxceed). Both doses restored fast axonal transport in spinal axons, wherein MT numbers and stable (detyrosinated) tubulins were increased, compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
312
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 371 publications
(320 citation statements)
references
References 24 publications
5
312
1
2
Order By: Relevance
“…While other mechanisms cannot be excluded, the aforementioned sciatic nerve deficits may critically contribute to motor deficits found in old Tau−/− as fine‐tuning of myelin sheath thickness and formation is important for maintenance and proper function of motor fibers. In addition, while no amplitude differences in muscle action potentials of Tau−/− were found, further studies are needed to clarify the impact of loss of Tau on neuromuscular junction by aging as Tau‐related pathology in motor neurons has been shown to have neuromuscular junction malfunction and motor deficits in AD Tg models (Zhang et al ., 2005; Ubhi et al ., 2007). …”
Section: Discussionmentioning
confidence: 99%
“…While other mechanisms cannot be excluded, the aforementioned sciatic nerve deficits may critically contribute to motor deficits found in old Tau−/− as fine‐tuning of myelin sheath thickness and formation is important for maintenance and proper function of motor fibers. In addition, while no amplitude differences in muscle action potentials of Tau−/− were found, further studies are needed to clarify the impact of loss of Tau on neuromuscular junction by aging as Tau‐related pathology in motor neurons has been shown to have neuromuscular junction malfunction and motor deficits in AD Tg models (Zhang et al ., 2005; Ubhi et al ., 2007). …”
Section: Discussionmentioning
confidence: 99%
“…221 Weekly taxol treatment of tau transgenic mice over 12 weeks restored fast anterograde transport, increased the number of axonal microtubules, and diminished motor deficits. 222 Other microtubule-stabilizing approaches are reviewed by Michelis et al 223,224 The neuronal tubulin-preferring agent NAP was reported to display less side effects than the non-cell-typespecific taxol, which inhibits cell mitosis in general. 225 The octapeptide NAPVSIPQ (NAP) has a preference for neuronal tubulin and crosses the BBB readily when administered intranasally.…”
Section: Microtubule-stabilizing Drugsmentioning
confidence: 99%
“…This adversely affects cell function because the shortening and lengthening of microtubules (dynamic instability) is necessary for their function as a mechanism to transport other cellular components (e.g., the mitosis where microtubules position the chromosomes during their replication and subsequent separation into the two daughter-cell nuclei). Despite these adverse effects, low doses of paclitaxel may have a therapeutic benefit in human tauopathies by offsetting the loss of normal tau functions that result from its hyperphosphorylation and sequestration into tangles (Zhang et al 2005). …”
Section: Induction Of Abnormal Phosphorylation Of Tau By Paclitaxel Amentioning
confidence: 99%